Prevención no farmacológica de las exacerbaciones en la EPOC: efecto antiinflamatorio de la actividad física - Mendoza I., Laura; Guerrero P., Julia (Revista Hospital Clínico Universidad de Chile, 2019)
The chronic obstructive pulmonary disease (COPD) is the chronic respiratory condition most prevalent in adults, caused mainly by smoking. Its burden is progressively increasing and, according to the World Health Organization, is one of the main causes of mortality and disability around the world. Patients with COPD present acute worsening of the disease, defined as acute exacerbations, which are the main cause of hospitalizations and deaths. Therefore, it is crucial to identify effective interventions focused in their prevention. Patients with COPD present dyspnoea and intolerance to exercise responsible for a progressive reduction in the level of physical activity, which is an independent risk factor for future exacerbations and mortality. On the other hand, it has been demonstrated that COPD patients with low level of physical activity present higher marker levels of systemic inflammation. Interventions able to increase the level of physical activity in COPD patients have demonstrated positive effects in quality of life and a few clinical trials suggest that improving physical activity is able to prevent exacerbations. We hypothesize that these effects could be explained by changes in systemic inflammation secondary to an increase of physical activity.